(untitled) (The Pakistan Development Review, 1994)
An efficient and liberalised fmancial sector is essential for promoting economic growth and welfare. The process of fmancial liberalisation through "deepening" and eliminating distortion and segmentation of financial markets improves the process of the mobilisation of savings as well as the efficiency of investment, thereby accelerating the overall rate of economic growth. At the end of 1989 Pakistan undertook an ambitious financial sector reforms programme with the aim to improve the effectiveness of monetary policy through greater reliance on market forces. The main liberalisation policies were aimed at liberalising interest rates, reducing controls on credit, enhancing competition and efficiency in the fmancial system, strengthening the supervisory framework, and promoting the growth and deepening of fmancial markets.